Association of brain derived neurotrophic factor (BDNF) with inflammation in psoriasis - Moqaddasi, Hamidraza; Dubey, Ashok Kumar; Goel, Shitij; Dubey , Suparna; Maddali, Gopi Krishna (Asian Journal of Medical Sciences, 2020)
Background: Psoriasis is a common immune mediated chronic inflammatory disorder characterized by involvement of skin and other organ systems. Brain derived neurotrophic factor (BDNF) which has various roles in the nervous system, is also involved in cutaneous sensory innervation. Apremilast is a relatively new drug indicated for moderate-to-severe plaque psoriasis and psoriatic arthritis. Aims and Objective: The present study aimed to explore the BDNF levels in moderate to severe plaque psoriasis and analyse the variation in the levels, if any, in response to apremilast therapy. Materials and Methods: Blood samples from patients of psoriasis (n=24), of either sex and age ≥18 years suitable to be prescribed apremilast as standard treatment, were taken on initial and subsequent follow up visit after two months of therapy. Sample from matched controls were also evaluated. Enzyme-linked immunosorbent assay (ELISA) kit (QUAYEE-BIO) and microplate reader (at 450 nm) were used to determine BDNF values. Sample concentrations in each plate were calculated from standard curves and dilution factors. Results: The BDNF values in healthy controls had a mean of 25.14 ± 14.21 ng/mL. The baseline values in the patients had a mean of 72.49± 9.05 ng/mL. The values in the patients after apremilast therapy had a mean of 63.60± 9.53 ng/mL. Conclusion: BDNF levels are significantly increased in patients with moderate to severe plaque psoriasis. Apremilast therapy significantly reduced the raised BDNF levels in such patients, though the reduced level was still significantly higher than the levels in normal healthy controls. Rather than being linked to any neurobehavioral component, the BDNF levels predominantly appear to be linked to the underlying inflammation in psoriasis.